1998
DOI: 10.1172/jci592
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-dependent homotypic adhesion of neutrophils. Arachidonic acid activates Raf-1/Mek/Erk via a 5-lipoxygenase- dependent pathway.

Abstract: AA stimulates integrin-dependent neutrophil adhesion, a critical early step in acute inflammation. However, neither the signaling pathway(s) of AA-stimulated adhesion, nor whether AA acts directly or through the generation of active metabolites, has been elucidated. Previously, we have observed a tight association between neutrophil Erk activation and homotypic adhesion in response to chemoattractants acting through G protein-linked receptors. We now report a similar association between homotypic adhesion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
57
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 65 publications
7
57
1
Order By: Relevance
“…The mechanism of this inhibition was not determined, but probably relates to the ability of E-prostanoid 2 receptors to activate adenyl cyclase, leading to cAMP accumulation, protein kinase A (PKA) activation, and ERK pathway inhibition at the level of Raf-1 interaction with 14-3-3 proteins (51)(52)(53). Consistent with such a model, E-series PGs inhibit ERK in neutrophils in a cAMP-and PKA-dependent fashion (23,54,55). In FLSCs, we have observed that the cell-permeable cAMP analog dibutyryl cAMP inhibited IL-1␤/TNF-␣-stimulated ERK activation (M.H.P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this inhibition was not determined, but probably relates to the ability of E-prostanoid 2 receptors to activate adenyl cyclase, leading to cAMP accumulation, protein kinase A (PKA) activation, and ERK pathway inhibition at the level of Raf-1 interaction with 14-3-3 proteins (51)(52)(53). Consistent with such a model, E-series PGs inhibit ERK in neutrophils in a cAMP-and PKA-dependent fashion (23,54,55). In FLSCs, we have observed that the cell-permeable cAMP analog dibutyryl cAMP inhibited IL-1␤/TNF-␣-stimulated ERK activation (M.H.P.…”
Section: Discussionmentioning
confidence: 99%
“…However, ERK may also be activated in response to proinflammatory stimuli (22,23). For example, Vilcek and colleagues (24 -26) have demonstrated that in FS-4 fibroblasts, ERK undergoes activation in response to the cytokines IL-1␤ and TNF-␣, both of which are critical to the pathogenesis of RA.…”
mentioning
confidence: 99%
“…A recent report indicates that AA, acting as a second messenger, is able to stimulate the phosphorylation and activity of ERK in a variety of cell types including human neutrophils [20]. The activation of ERK by AA through an LO-dependent but COX-independent pathway has been reported in vascular smooth muscle cells [21] and in human neutrophils [22]. The inability of BW755C, a dual inhibitor of COX and LO [23], to prevent ERK activation by fMLP in rat neutrophils ( Fig.…”
Section: Phosphorylation Of Erk Via a G Protein-dependent Andmentioning
confidence: 98%
“…Oxygen-derived free radicals induce activation of ERK1/2 and a second MAP kinase, p38 in cardiac myocytes and other cells (23,24). H 2 O 2 -induced activation of ERK1/2 is mediated through the Ras/Raf-1/Mek pathway (23)(24)(25). PD098059, a selective inhibitor of ERK1/2 activation, aggravates H 2 O 2 -induced apoptosis of cardiomyocytes (23).…”
mentioning
confidence: 99%